A Multistep Workflow to Evaluate Newly Generated iPSCs and Their Ability to Generate Different Cell Types - Chen, Carol X.-Q.; Abdian, Narges; Maussion, Gilles; Thomas, Rhalena A.; Demirova, Iveta; Cai, Eddie; Tabatabaei, Mahdieh; Beitel, Lenore K.; Karamchandani, Jason; Fon, Edward A.; Durcan, Thomas M. (Methods and protocols, 2021)
Induced pluripotent stem cells (iPSCs) derived from human somatic cells have created new opportunities to generate disease-relevant cells. Thus, as the use of patient-derived stem cells has become more widespread, having a workflow to monitor each line is critical. This ensures iPSCs pass a suite of quality-control measures, promoting reproducibility across experiments and between labs. With this in mind, we established a multistep workflow to assess our newly generated iPSCs. Our workflow tests four benchmarks: cell growth, genomic stability, pluripotency, and the ability to form the three germline layers. We also outline a simple test for assessing cell growth and highlight the need to compare different growth media. Genomic integrity in the human iPSCs is analyzed by G-band karyotyping and a qPCR-based test for the detection of common karyotypic abnormalities. Finally, we confirm that the iPSC lines can differentiate into a given cell type, using a trilineage assay, and later confirm that each iPSC can be differentiated into one cell type of interest, with a focus on the generation of cortical neurons. Taken together, we present a multistep quality-control workflow to evaluate newly generated iPSCs and detail the findings on these lines as they are tested within the workflow.